Sustainability business in the culinary sector: A systematic literature review - Yudawisastra, Helin G; Layalia, Faza (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2025)
Background: Business sustainability issues arise in the culinary sector due to the need to balance growth with environmental, social, and economic impacts. The purpose of this study is to analyze the business strategies used by culinary businesses to achieve sustainability. Methods: This research uses the Systematic Literature Review (SLR) method with the PRISMA protocol. Literature searches were conducted on the Google Scholar database using keywords such as